Prácticas de simulación y programación del mini PLC LOGO con fines didácticos. - Curimilma Huanca, Juan Hernán (2012)
The research was formalized en the framework of the thesis: "PRACTICES OF SIMULATION AND PROGRAMMING THE MINI PLC LOGO WITH TEACHING PURPOSES" through the use of the Software LOGO! Soft Comfort V6.1 The practices of simulation and programming the MINI PLC LOGO establish a teaching guide for the students in the career of the technology race in electricity and industrial control. Was the acquisition of computers and software respectively. This group of computers it is the implement Electronic Laboratory, the Area of Energy Industries and Natural Resources Non Renewable, at the NATIONAL UNIVERSITY OF LOJA, with the objective of ensuring that students and teachers they can design, program and simulate automation applications. It should be noted that such practices they can be performed in real and virtual, in this case it will be for virtual that we will have interactive simulations, planned and executed based on the software in a PC. The software has as main function, simulate electrical circuits, digital or electronic. These applications, in the post if required will be applied in the industrial field using an electronic device called PLC (LOGICAL CONTROL PROGRAM). The methodology used for the development of this work, Is the use of analytical method, by which allows us to know more the object of study, with which you can: explain, make analogies, to better understand their behavior and establishing new theories. As mentioned above there will be a guide that will allow, realize efficiently several practices according to the model designed. Therefore it is recommended that the student can read the guide.